Pengaruh Pelayanan dan Fasilitas Perpustakaan Terhadap Minat Membaca Siswa - Iis Delis (Program Studi Manajemen Pendidikan Islam Institut Agama Islam Sunan Kalijogo Malang, 2021)
This study aims 1) to determine the effect of services on students' reading interest, 2) to determine library facilities on students' reading interest, 3) to determine the effect of library services and facilities on students' reading interest. This research was conducted at SMA Negeri 4 Pandeglang. In this study the method used is a quantitative method. The population in this study were all students of SMA Negeri 4 Pandeglang with a total of 1284 students. Samples were taken as many as 100 students using the Slovin formula with an error rate of 10% and using the Proportional Random Sampling technique as a sampling technique. The data collection instrument was in the form of a questionnaire or questionnaire. The instrument test phase was carried out by using validity and reliability tests. To analyze using the average value, standard deviation, normality test, linearity test, multiple regression test, hypothesis test t and hypothesis test f. Based on the results showed that the multiple linear regression equation is Y = 24.573 + 0.234 + 0.352. This shows that there is a positive influence of library services and facilities on students' reading interest in SMA Negeri 4 Pandeglang,